Stylet jaws of Chrysopetalidae (Annelida) - Watson, Charlotte; Faulwetter, Sarah (Journal of Natural History, 2017)
Micro-CT imaging elucidates jaw and pharynx structure in 14 nominal taxa belonging to Chrysopetalinae, Dysponetinae and Calamyzinae (Chrysopetalidae: Annelida). Systematic evaluation of chrysopetalid jaw form in each taxon is used to compare inter-generic relationships within and between each subfamily and with other polychaete families possessing lateral pairs of jaws. Jaw morphology proves diagnostic at all levels including agreement with current molecular phylogenetic analyses of the Chrysopetalidae. The greatest diversity of pharynx and jaw form, associated with sensory body characters, is found amongst taxa of the epibenthic Chrysopetalinae. It is hypothesized that the paired stylet jaws interlock to pierce prey tissue, and, in concert with a highly muscular pharynx, suck out prey fluids that pass down the internal groove of the stylets. Three generic groups are identified based on congruence of jaw form, and novel buccal structures are revealed in some taxa: a pharyngeal calcareous ?ring? and extensive pharyngeal glands. A continuum across free-living and facultative symbiont lifestyles is represented across all Chrysopetalinae. Dysponetinae comprises free-living, very small individuals that exhibit a meiofaunal lifestyle. All species possess one type of simple, tanned rod-like stylet jaws and certain simplified body structures. Calamyzinae species possess polyphyletic jaw forms and grades of radically simplified sensory morphologies. Free-living, bacteriovore calamyzins inhabit extreme chemosynthetic habitats and lack jaws, or possess modified jaws composed of an anterior platelet and posterior grooved jaw, present in the larvae and lost in the adult. New observations of an ectoparasitic Calamyzinae include details of a specialized mouth opening and stylet jaw present in a species that exhibits cryptic coloration, while grooved jaws are revealed for the first time in an obligate symbiont calamyzin. The grooved jaw form is considered a non-homoplasious synapomorphy that supports the monophyly of the family Chrysopetalidae.
World Polychaeta Database (WPolyDb), online before print, 24 Nov 2017